El establecimiento de la industria de yuca seca en la Costa Atlantica de Colombia - Best, R.; Sarria, H.; Ospina, B. (International Center for Tropical Agriculture, 1991)
Technical and administrative aspects of the cassava natural drying project on the Atlantic Coast of Colombia and its process of development are reviewed. The project, now in its 10th yr, has undergone 3 phases: the exptl. phase 1981 (building of natural drying plant, adapting of processing technology, developing of operational scheme); the demostration phase 1982/83 (semicommercial operation of the pilot plant with farmers fully responsible for plant management; and replication phase 1983 onward (establishment of more than 40 drying plants at other sites on the Atlantic Coast). Details are also provided on the small-scale drying technology for chipping and natural drying of roots. Likewise, institutional relationships and interactions within the rural development project are examined. The pilot project brought important benefits to 3 principal groups of people involved: farmers, development agents, and researchers. This project has served as a model for carrying out similar projects in other Latin American countries. Results to date have shown the effectiveness of the pilot project concept to ensure that researchers and development agents responsible for generating and transferring technology will work together with the farmer to generate viable solutions to their problems. (CIAT)